2015
DOI: 10.1080/0013791x.2015.1062582
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based costing for early phase life cycle cost analysis: Example application to an environmental remediation project

Abstract: Simulation-based costing (SBC) has been slow to be adopted by the traditional cost estimating community. This can be attributed to many factors, including complexity, how to gather data and develop probabilistic inputs, cost of SBC software, and a lack of understanding of the benefits of developing cost versus risk profiles. This article presents an overview of how SBC can be effectively utilized for early phase life cycle cost (LCC) estimation. A formal process for conducting LCC incorporating SBC is present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Cost modeling showed that the cost drivers were the soil volume to be remediated, the percentage of DU, and the size of the area to be remediated. Comparing various treatment options, the cost model showed the lowest cost for remediation to be selective excavation of the contaminated soil followed by physical separation of that soil and chemical treatment of the residual soil fines (Farr et al 2016;Walters et al 2014).…”
Section: Treatment Of Du-contaminated Soilmentioning
confidence: 99%
“…Cost modeling showed that the cost drivers were the soil volume to be remediated, the percentage of DU, and the size of the area to be remediated. Comparing various treatment options, the cost model showed the lowest cost for remediation to be selective excavation of the contaminated soil followed by physical separation of that soil and chemical treatment of the residual soil fines (Farr et al 2016;Walters et al 2014).…”
Section: Treatment Of Du-contaminated Soilmentioning
confidence: 99%
“…Thus, environmental decision-making typically involves complex problems possessing objectives and design requirements that are very difficult to capture when their supporting decision models are formulated (Hipel and Ben-Haim, 1999;Mowrer, 2000;De Kok and Wind, 2003;Brugnach et al, 2007;Matthies et al, 2007;Fuerst et al, 2010;Hipel and Walker, 2011;Castelletti et al, 2012;Lund, 2012;Walker et al, 2012). Environmental planning becomes even more complicated when the system components contain extensive stochastic uncertainties (Baetz, 1990;Yeomans, 2008;Gunalay et al, 2012;Farr et al, 2016;Han et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The most used approach to deal with inherent (aleatory) uncertainty is the Montecarlo simulations (MCS) [29]. Farr et al [30] argued about the usefulness of simulation-based costing during initial phases of system design, because that is when budgets are set. However, these simulation experiments require substantial data to compound useful and representative probability distributions [31].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, fuzzy mathematics has been used when the available data was limited. Comparing both techniques, the authors found that fuzzy mathematics is a more conservative approach for risk assessment than MCS [30]. In an attempt to improve the accuracy of the LCC models, the activity-based costing approach has been included into LCC models.…”
Section: Introductionmentioning
confidence: 99%